2021
DOI: 10.1111/cea.14003
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dipeptidyl peptidase 10 to airway dysfunction in patients with NSAID‐exacerbated respiratory disease

Abstract: Background: Genetic variants of dipeptidyl peptidase 10 (DPP10) have been suggested to contribute to the development of NSAID-exacerbated respiratory disease (NERD). However, the mechanisms of how DPP10 contributes to NERD phenotypes remain unclear. Objective: To demonstrate the exact role of DPP10 in the pathogenesis of NERD. Methods: Patients with NERD (n = 110), those with aspirin-tolerant asthma (ATA, n = 130) and healthy control subjects (HCs, n = 80) were enrolled. Clinical characteristics were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Dipeptidyl peptidase 10 (DPP10) expressed in the airway epithelium is associated with asthma and lung function decline. 65 66 Higher serum DPP10 levels negatively correlated with FEV1% in patients with NERD than in those with ATA ( Table ). Furthermore, a positive correlation was observed between serum levels of DPP10 and TGF-β1 in patients with NERD.…”
Section: Biomarkers Related To Inflammatory Cells and Cytokinesmentioning
confidence: 97%
See 1 more Smart Citation
“…Dipeptidyl peptidase 10 (DPP10) expressed in the airway epithelium is associated with asthma and lung function decline. 65 66 Higher serum DPP10 levels negatively correlated with FEV1% in patients with NERD than in those with ATA ( Table ). Furthermore, a positive correlation was observed between serum levels of DPP10 and TGF-β1 in patients with NERD.…”
Section: Biomarkers Related To Inflammatory Cells and Cytokinesmentioning
confidence: 97%
“…Furthermore, a positive correlation was observed between serum levels of DPP10 and TGF-β1 in patients with NERD. 65 A genome-wide association study (GWAS) demonstrated the significant association of a single nucleotide polymorphism in DPP10 with NERD. 66 67 These findings have suggested that DPP10 could contribute to the decline in the lung function in NERD.…”
Section: Biomarkers Related To Inflammatory Cells and Cytokinesmentioning
confidence: 99%
“…Serum levels of TGF‐β1 were significantly higher in NERD patients than in ATA and positively correlated with urinary LTE4 levels 101 . Moreover, serum levels of dipeptidyl peptidase 10 (DDP10) may be also a potential biomarker to distinguish NERD from ATA and predict disease severity as a positive correlation has been found with TGF‐β1 in patients with NERD 102 …”
Section: Biomarkers In Nsaids Cross‐hypersensitivitymentioning
confidence: 99%
“…101 Moreover, serum levels of dipeptidyl peptidase 10 (DDP10) may be also a potential biomarker to distinguish NERD from ATA and predict disease severity as a positive correlation has been found with TGF-β1 in patients with NERD. 102 Surfactant protein D (SPD) interacts with phagocytic cells attenuating airway inflammation and remodelling. Therefore, serum SPD levels were lower and negatively correlated with FEV1% decrease after aspirin challenges in patients with NERD than with ATA.…”
Section: B I Omark Er S In N Saids Cross -Hyper Sen Sit Ivit Ymentioning
confidence: 99%
“…In addition to mediators related to immune cells, epithelium-derived cytokines, including IL-25, IL-33, and TSLP, which subsequently induce activation of group 2 innate lymphoid cells (ILC2s), have been emphasized in SA with persistent eosinophilic airway inflammation ( 18 ). Furthermore, close interplays between airway epithelial cells (AECs) and immune cells (increased levels of folliculin and dipeptidyl peptidase 10, but decreased levels of surfactant protein D) could induce airway inflammation, and remodeling has been demonstrated in patients with aspirin-exacerbated respiratory disease (AERD), a phenotype of SA ( 19 20 21 22 23 24 25 ). Although many molecules have been highlighted in type 2 asthma related to disease severity, recent biologics under clinical trials mainly focus on targeting IL-4, IL-5, IL-33, and TSLP.…”
Section: Asthma Phenotypesmentioning
confidence: 99%